Estetika Fotografi Ipphos Selama Periode Revolusi Fisik (1945-1949) Di Indonesia Sebagai Media Propaganda Dan Alat Diplomasi Melalui Pembacaan Semiotik - Ferdiansyah; I Wayan Adnyana; I Wayan Mudana; I Made Bayu Pramana (Kartala Virtual Studies, 2026)
Photography has a very significant role in the course of Indonesian history. Initially, photography was only seen as a form of documentation, but over time, it transformed into a medium of propaganda and a tool of diplomacy. The focus of this study is photographs produced by IPPHOS (Indonesia Press Photo Service), which primarily include photos of the reading of the proclamation text, the raising of the red and white flag on August 17, 1945, and Soekarno-Hatta embracing Soedirman. The purpose of this study is to explore the power and potential of photography as a medium of propaganda and a tool of diplomacy. Based on its function, photography was considered a form of aesthetics during the physical revolution. This study will analyze the role of photography as a tool of propaganda and diplomacy of the Indonesian government during the revolution by highlighting the aesthetic elements in IPPHOS photographs, which reflect the strategy of the struggle to maintain independence between 1945 and 1949. The methodology used in this study is a qualitative approach, with a semiotic analysis of photographs identified as a medium of propaganda and a tool of diplomacy by the Indonesian government during the Physical Revolution period. This study aims to understand how photographs from the Physical Revolution period function as visual codes that convey messages, both verbally and non-verbally. By analyzing the meaning of signifiers-signified, it is hoped that the postcolonial generation can understand and analyze the history of Indonesian photography. Keywords: Photography, Propaganda, Diplomacy, IPPHOS, Physical Revolution, Semiotics.